Scaling Up Fodder Innovations to Catalyse Agricultural Systems Transformation in Southern Ethiopia - Shilomboleni, Helena; Demeke, Getamesay; Recha, John W.M.; Ambaw, Gebermedihin; Mohammed, Yasin; Laulhere-Vigneau, Anne; Abera, Wuletawu; Tamene, Lulseged D.; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This InfoNote shares project experiences of scaling up fodder production in southern Ethiopia as an entry point to catalysing agricultural systems resilience and landscape transformation. • The fodder innovations build on 20 years of experimentation on soil & water conservation work in the region by Inter-Aide and various development partners to refine the design and delivery of the technology. • Earlier versions of the technology, however, saw low adoption in part due to limited engagement with social relations to translate innovation into a perceived relevant opportunity for end-users. • Over time, Inter Aide leveraged and strengthened the capacity of various local stakeholders to stimulate community ownership of fodder innovations work and to ensure consistent implementation at watershed levels. • The process has empowered local actors to champion the scaling of fodder innovations and more, in ways that leverage the agency of beneficiaries to catalyse action on systems change in the management and preservation of natural resources.